2022
DOI: 10.3390/brainsci12101348
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Perspective Feature Extraction and Fusion Based on Deep Latent Space for Diagnosis of Alzheimer’s Diseases

Abstract: Resting-state functional magnetic resonance imaging (rs-fMRI) has been used to construct functional connectivity (FC) in the brain for the diagnosis and analysis of brain disease. Current studies typically use the Pearson correlation coefficient to construct dynamic FC (dFC) networks, and then use this as a network metric to obtain the necessary features for brain disease diagnosis and analysis. This simple observational approach makes it difficult to extract potential high-level FC features from the represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The former was based on dynamically intercepting signals through windows of specific length and then performing functional connectivity analysis within each dynamic window. In recent years, a number of studies have been devoted to the extraction of high-level features from the dFC to achieve effective filtering of invalid information in the dFC and extraction of dynamic change features associated with the disease, contributing to exploring abnormal brain function networks and improving the classification accuracy of AD ( Sendi et al, 2021 ; Gao et al, 2022 ; Matsui and Yamashita, 2022 ; Qiao et al, 2022 ; Ghanbari et al, 2023 ; Penalba-Sánchez et al, 2023 ). The principle of CAP was to extract co-activation patterns in certain specific peak points of the BOLD signal time series using a clustering algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The former was based on dynamically intercepting signals through windows of specific length and then performing functional connectivity analysis within each dynamic window. In recent years, a number of studies have been devoted to the extraction of high-level features from the dFC to achieve effective filtering of invalid information in the dFC and extraction of dynamic change features associated with the disease, contributing to exploring abnormal brain function networks and improving the classification accuracy of AD ( Sendi et al, 2021 ; Gao et al, 2022 ; Matsui and Yamashita, 2022 ; Qiao et al, 2022 ; Ghanbari et al, 2023 ; Penalba-Sánchez et al, 2023 ). The principle of CAP was to extract co-activation patterns in certain specific peak points of the BOLD signal time series using a clustering algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Venugopalan et al ( 2021 ) used stacked de-noising auto-encoders to extract features from clinical and genetic data of AD, and used CNN for imaging data, then found that hippocampus, amygdala brain areas and the rey auditory verbal learning test (RAVLT) were significant changes in AD brain. Despite variable structures of CNNs, the deep features extracted from CNNs were used to explain their strong recognition power (Bi et al, 2020 ; Gao et al, 2022 ). One aim of this study was to find possible explanations of the learned features based on the connectivity matrices derived from PSI matrix of fMRI signals.…”
Section: Introductionmentioning
confidence: 99%
“…Vaithinathan et al designed a new magnetic resonance T1-weighted texture extraction technique for Alzheimer's disease classification for early AD diagnosis, starting from the texture of the brain, and achieved good classification results [21].In addition to this, the literature combines 2D images and 3D images to perform studies on the early diagnostic classification of AD [22,23].Bi X et al designed two deep learning methods for functional brain network classification. The convolutional learning method learns deep region connectivity features and the recursive learning method learns deep adjacency location features, in addition, an Extreme Learning Machine (ELM) enhancement structure was implemented to further improve the learning capability, and the results show that the proposed method provides satisfactory learning capability in AD detection applications [24].Kanghan et al used unsupervised learning based on convolutional autoencoders (CAE) to solve AD and NC classification tasks and supervised transfer learning to solve pMCI and sMCI classification tasks [25].In addition there is the application of autoencoders in combination with long and short-term memory networks to resting-state functional magnetic resonance imaging for the early diagnosis of Alzheimer's disease [26].…”
Section: Introductionmentioning
confidence: 99%